The Soviet mind Russian culture under communism - Berlin, Isaiah 1909-1997 (The Brookings classics, 2016)
"With a revised foreword by Brookings President Strobe Talbott and a new introduction by Berlin's editor, Henry Hardy. George Kennan, the architect of US policy toward the Soviet Union, called Isaiah Berlin 'the patron saint among the commentators of the Russian scene.' In The Soviet Mind, Berlin proves himself fully worthy of that accolade. Although the essays in this book were originally written to explore the tensions between Soviet communism and Russian culture, the thinking about the Russian mind that emerges is as relevant today under Putin's post-communist Russia as it was when this book first appeared more than a decade ago. This Brookings Classic brings together Berlin's writings about the Soviet Union. Among the highlights are accounts of Berlin's meetings with the Russian writers in the aftermath of the war; a celebrated memorandum he wrote for the British Foreign Office in 1945 about the state of the arts under Stalin; Berlin's account of Stalin's manipulative 'artificial dialectic'; portraits of Pasternak and poet Osip Mandel'shtam; Berlin's survey of Russian culture based on a visit in 1956; and a postscript reflecting on the fall of the Berlin Wall and other events in 1989. Henry Hardy prepared the essays for publication; his introductory discussions describe their history. In his foreword, revised for this new edition, Brookings's Strobe Talbott, a long-time expert on Russia and the Soviet Union, relates the essays to Berlin's other work. The essays and other pieces in The Soviet Mind-which includes a new essay, 'Marxist versus Non-Marxist Ideas in Soviet Policy,' and a summary of a talk on communism-represent Berlin at his most brilliant, and are invaluable for policy-makers, students and anyone interested in Russian politics and thought-past, present and future"...